Critical virtuality in the university classroom in the pandemic (and beyond) - D'Antoni, Maurizia (2020)
This document aims to return to the reactions and difficulties of approach, in the pandemic, to the training processes mediated by virtuality at the University of Costa Rica. In the midst of uncertainty, one of the teachers' reactions was the rejection of remote teaching modalities; Therefore, it is intended to show two positive aspects of the use of virtual platforms in training: accessibility and the promotion of student self-regulation. Because of the newness and novelty of the situation, the search will use the experience and personal position.